Effects of Pictorial Medication Label on Medication Using Behaviors among Illiterate Hypertensive Elders: a Case Study in a Muslim Community of Pattani Province - ประทีปเกาะ ฐปนรรฆ์; กูดาโตะมูลียอ นิอิดรุส; คงหนู ศรีสุดา; อิสอ มายือนิง (Journal of Health Science of Thailand, 2022)
Hypertensive patients need long-term correct medications to reduce premature deaths or complications. Medication labels are communication tools for proper use of medicines. This quasiexperimental one group pretest and posttest design was aimed to compare the effects of pictorial labels on medication using behaviors among the low-illiterate hypertensive elders. The study samples were 30 Muslim elders with diagnosed hypertension and low-literacy who were randomly selected into the study. The instruments used in the study were the pictorial medication label, participatory designed by local health care teams and the structured-interview form. A paired t-test was used to compare the average scores of behaviors before and after intervention. The results revealed that the median age of the samples was 71 years (IQR 79, 65.2), and most of them were female (86.7%). The pictorial aids improved the mean scores of medication uses and reduced medication errors. The overall mean score of behaviors in medication uses after intervention (Mean=56.3, SD=3.7) was significantly better than before (Mean=44.1, SD=3.6) (p<0.05). Thus, a pictorial label is an optional aid in the improvement of positive medication uses among hypertensive elders with low-literacy.